(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This article reviews mathematical model for the determination of friction coefficient for lubricated surfaces which operate works at sliding friction pairs in boundary lubrication case. In the particular model an absolutely smooth ball and rough surface contact is viewed taking into account properties of the material, surface roughness parameters, lubricating material kinematic viscosity and density. The model refers to widely spread ball-on-disc type tribometer where ball is in the contacts with plane.